Aedes aegypti and Aedes albopictus Habitat Preferences in South Texas, USA - Samantha R. Champion; Christopher J. Vitek (SAGE Publishing, 2014)
The South Texas region has a historical record of occasional dengue outbreaks. The recent introduction of chikungunya virus to the Caribbean suggests that this disease may be a concern as well. Six different cities and three field habitat types (residential, tire shops, and cemeteries) were examined for evidence of habitat and longitudinal preference of two vector species, Aedes aegypti and Aedes albopictus. A. aegypti was more prevalent in tire shop sites, while A. albopictus was more prevalent in cemetery sites. In residential sites, the relative abundance of the two species varied with longitude, with A. albopictus being more abundant near the coast, and A. aegypti being more abundant inland. There was also a temporal variation, with A. aegypti declining in frequency over time in residential sites. These results have implications for control strategies and disease risk and suggest a greater need for increased surveillance and research in the region.